The global burden of hemorrhagic stroke: a summary of findings from the GBD 2010 study. - Krishnamurthi, R; Moran, A; Forouzanfar, M; Bennett, D; Mensah, G; Lawes, C; Barker-Collo, S; Connor, M; Roth, G; Sacco, R; Ezzati, M; Naghavi, M; et al. (2014)
This report summarizes the findings of the GBD 2010 (Global Burden of Diseases, Injuries, and Risk Factors) study for hemorrhagic stroke (HS). Multiple databases were searched for relevant studies published between 1990 and 2010. The GBD 2010 study provided standardized estimates of the incidence, mortality, mortality-to-incidence ratios (MIR), and disability-adjusted life years (DALY) lost for HS (including intracerebral hemorrhage and subarachnoid hemorrhage) by age, sex, and income level (high-income countries [HIC]; low- and middle-income countries [LMIC]) for 21 GBD 2010 regions in 1990, 2005, and 2010. In 2010, there were 5.3 million cases of HS and over 3.0 million deaths due to HS. There was a 47% increase worldwide in the absolute number of HS cases. The largest proportion of HS incident cases (80%) and deaths (63%) occurred in LMIC countries. There were 62.8 million DALY lost (86% in LMIC) due to HS. The overall age-standardized incidence rate of HS per 100,000 person-years in 2010 was 48.41 (95% confidence interval [CI]: 45.44 to 52.13) in HIC and 99.43 (95% CI: 85.37 to 116.28) in LMIC, and 81.52 (95% CI: 72.27 to 92.82) globally. The age-standardized incidence of HS increased by 18.5% worldwide between 1990 and 2010. In HIC, there was a reduction in incidence of HS by 8% (95% CI: 1% to 15%), mortality by 38% (95% CI: 32% to 43%), DALY by 39% (95% CI: 32% to 44%), and MIR by 27% (95% CI: 19% to 35%) in the last 2 decades. In LMIC countries, there was a significant increase in the incidence of HS by 22% (95% CI: 5% to 30%), whereas there was a significant reduction in mortality rates of 23% (95% CI: -3% to 36%), DALY lost of 25% (95% CI: 7% to 38%), and MIR by 36% (95% CI: 16% to 49%). There were significant regional differences in incidence rates of HS, with the highest rates in LMIC regions such as sub-Saharan Africa and East Asia, and lowest rates in High Income North America and Western Europe. The worldwide burden of HS has increased over the last 2 decades in terms of absolute numbers of HS incident events. The majority of the burden of HS is borne by LMIC. Rates for HS incidence, mortality, and DALY lost, as well as MIR decreased in the past 2 decades in HIC, but increased significantly in LMIC countries, particularly in those patients ≤75 years. HS affected people at a younger age in LMIC than in HIC. The lowest incidence and mortality rates in 2010 were in High Income North America, Australasia, and Western Europe, whereas the highest rates were in Central Asia, Southeast Asia, and sub-Saharan Africa. These results suggest that reducing the burden of HS is a priority particularly in LMIC. The GBD 2010 findings may be a useful resource for planning strategies to reduce the global burden of HS.